Impact of nutritious meals on the nutritional status of the tribal students: A comparison between centralized kitchens (Annapurna) and regular kitchens in government tribal residential schools from two Districts of Maharashtra, India - Rajagopal Devara; Devika Deshmukh (Wolters Kluwer Medknow Publications, 2017)
Background: Tackling undernutrition is a global priority. It is the single largest risk factor influencing the burden of disease estimates at the global level. The Annapurna Project was undertaken by Government of Maharashtra to provide nutritious meals to Ashram/residential tribal school students through a centralized kitchen for achieving optimal growth and development and to prevent morbidity. Objectives: The primary objective of our work was to ascertain whether the provision of nutritious meals through centralized kitchens improves the proportion of underweight and stunted children. Methods: We used a cluster trial with parallel intervention and control arms. The allocation ratio was 1:1 for participants in the intervention and control areas. The pilot was undertaken between 2015 and 2017. Tribal dominant Nashik and Palghar districts in Maharashtra were selected by the state government to implement the centralized kitchen plan. Results: At the baseline, the percentage of underweight children in the intervention group was 36.9% and 31.9% in the control groups. The percentage of stunting in the intervention group was 30.0% and 38.2% in the control group. At the endline, 21.9% and 26.3% of the children were underweight. Both groups showed an improvement as compared to the baseline. However, the difference in reduction between the intervention and the control group was insignificant. Similarly, stunting also reduced to 12.9% and 14.6% in the intervention and control groups, respectively. Conclusion: The provision of regular nutritious meals, through centralized and local kitchen in government tribal residential schools of Maharashtra is effective and important in tackling undernutrition in Tribal children.